Brief report: genetics of alcoholic cirrhosis : GenomALC multinational study - Whitfield, John B.; Rahman, Khairunnessa; Haber, Paul S.; Day, Christopher P.; Masson, Steven; Daly, Ann K.; Cordell, Heather J.; Mueller, Sebastian; Seitz, Helmut K.; Liangpunsakul, Suthat; Westerhold, Chi; Liang, Tiebing; et al. (Alcoholism, 2015)
Background The risk of alcohol-related liver cirrhosis increases with increasing alcohol consumption, but many people with very high intake escape from liver disease. We postulate that susceptibility to alcoholic cirrhosis has a complex genetic component and propose that this can be dissected through a large and sufficiently powered genomewide association study (GWAS). Methods The GenomALC Consortium comprises researchers from Australia, France, Germany, Switzerland, United Kingdom, and United States, with a joint aim of exploring the genetic and genomic basis of alcoholic cirrhosis. For this National Institutes of Health/National Institute on Alcohol Abuse and Alcoholism funded study, we are recruiting high-risk drinkers who are either cases (with alcoholic cirrhosis) or controls (drinking comparable amounts over similar time, but free of significant liver disease). Extensive phenotypic data are obtained using semistructured interviews and patient records, and blood samples are collected. Results We have successfully recruited 859 participants including 538 matched case-control samples as of September 2014, using study-specific inclusion-exclusion criteria and data collection protocols. Of these, 580 are cases (442 men and 138 women) and 279 are controls (205 men and 74 women). Duration of excessive drinking was slightly greater in cases than controls and was significantly less in women than men. Cases had significantly lower lifetime alcohol intake than controls. Both cases and controls had a high prevalence of reported parental alcohol problems, but cases were significantly more likely to report that a father with alcohol problems had died from liver disease (odds ratio 2.53, 95% confidence interval 1.31 to 4.87, p = 0.0055). Conclusions Recruitment of participants for a GWAS of alcoholic cirrhosis has proved feasible across countries with multiple sites. Affected patients often consume less alcohol than unaffected ones, emphasizing the existence of individual vulnerability factors. Cases are more likely to report liver disease in a father with alcohol problems than controls, consistent with a potential genetic component to the risk of alcoholic cirrhosis.
Gesehen am 01.07.2020